Development of a new partially restrained energy dissipater: Experimental and numerical analyses. (August 2018) - Liu, Ye; Wang, Chun-Lin; Wu, Jie
Abstract: Energy dissipaters constructed in structures play an important fuse-type role in concentrating damage and protecting the primary structure. A stable hysteretic behavior, easy fabrication and a low cost are expected characteristics of high-performance energy dissipaters. Previously studied energy dissipaters have disadvantages such as difficult grouting, insufficiently hysteretic capacity and low material utilization. In this paper, a new partially restrained energy dissipater consisting of an inner core bar and an outer partially restraining tube was developed. The inner core bar is milled along the longitudinal direction of the core bar, avoiding the adverse effects of grouting and welding and improving the utilization of the material. Parametric studies on geometrical variables were performed to investigate the low-cycle fatigue behaviors and deformation patterns of the proposed partially restrained energy dissipaters. Test results showed that the partially restrained energy dissipaters demonstrated stable hysteretic performance, and no local or overall buckling was observed. Design guidelines concerning the prevention of torsion buckling, control of section expansion and avoidance of local failure of the transitional segment were developed. The buckling responses, contact conditions and plastic deformations were analyzed via validated numerical models. Highlights: A newly developed partially restrained energy dissipater (PED) was investigated. PED has high material utilization and stable hysteretic behavior. Geometrical parameters have significant influence on PED. Develop design guidelines related to buckling, section expansion and local failure.